Difficulties in learning chemistry in high school, from the students' point of view and some alternatives to overcome them - Chonillo-Sislema, Luis (2024)
The study of Chemistry in high school often faces various difficulties that affect understanding and academic performance, which may arise from conceptual complexity, lack of connection with daily life, and traditional educational methodology. Objective: To understand the difficulties of students in learning Chemistry during high school, from their perspective, and to identify didactic alternatives used to overcome them. Methodology: A mixed approach with exploratory-descriptive scope, non-experimental, cross-sectional cohort was used, employing survey technique on the total sample (120 students), consisting of 12 thematic blocks and 12 items, aiming to understand the difficulties from students' perspective with a reliability of 0.835 in Cronbach's Alpha. Results: The results revealed that the most common difficulties include lack of motivation, abstraction of chemical concepts, topics requiring extensive memorization, exercises being too complex, and lack of practical application. Proposed alternatives include the use of more current examples in teaching chemistry, integration of active methodologies, didactic and digital resources, interactive scenarios (VR, AR), experimental activities, fostering a participative educational environment. Conclusion: It is essential to address the difficulties in teaching Chemistry through constant use of pedagogical strategies that promote participation and connection with everyday reality, which can significantly contribute to overcoming the identified challenges, thus improving the teaching and learning process of Chemistry in high school.